2020
DOI: 10.1111/jdv.16213
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends in hidradenitis suppurativa from 2008 to 2018

Abstract: Background Increased interest in hidradenitis suppurativa (HS) research is encouraging. A critical analysis of the state of HS literature may demonstrate the strength of existing knowledge and highlight current gaps. Objectives To analyse changes in HS literature from 2008 to 2018 with focus on quantity and quality of annual publications. Methods Review of all indexed publications reporting on HS on PubMed. Publications were categorized based on study design, study topic and treatment type where applicable. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…All studies eligible for inclusion were published within the last decade, which mirrors a general trend towards increased publication in HS research over the period, and the development of new treatments for the condition. 20,21 Diagnostic delay of HS is recognized as a global problem, with one international study across 24 countries showing patients with HS had an average diagnostic delay of 7Á2 years compared with an average diagnostic delay of 1Á6 years for patients with psoriasis. 22 A German study found that a longer delay in HS diagnosis was associated with greater disease severity, an increased number of surgically treated sites, concomitant diseases, and a higher number of days of work missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies eligible for inclusion were published within the last decade, which mirrors a general trend towards increased publication in HS research over the period, and the development of new treatments for the condition. 20,21 Diagnostic delay of HS is recognized as a global problem, with one international study across 24 countries showing patients with HS had an average diagnostic delay of 7Á2 years compared with an average diagnostic delay of 1Á6 years for patients with psoriasis. 22 A German study found that a longer delay in HS diagnosis was associated with greater disease severity, an increased number of surgically treated sites, concomitant diseases, and a higher number of days of work missed.…”
Section: Discussionmentioning
confidence: 99%
“…There were 14 studies included in our metasynthesis, which illustrated multiple challenges individuals face in living with HS and in seeking treatment and support. All studies eligible for inclusion were published within the last decade, which mirrors a general trend towards increased publication in HS research over the period, and the development of new treatments for the condition 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…HS research has grown exponentially over the last decade, signaling increased interest and commitment from researchers, clinicians, and funding agencies to advance this field [1, 2]. Most of the top-cited HS articles discuss medical treatments, a finding that is in line with HS being a difficult-to-treat medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has seen tremendous growth in HS research 8 coupled with a remarkable expansion in the therapeutic pipeline. 9 However, currently no single therapy for HS can guarantee satisfactory disease remission or durability of remission.…”
Section: Final Thoughtsmentioning
confidence: 99%